Religiosity’s impact on Political Participation: The Moderating Role of Social Awareness among Christian Millennials in Surabaya. - Lontoh Frederich Oscar Lambertus (Perichoresis: The Theological Journal of Emanuel University)
This study investigates the relationship between religiosity and political participation with Social Awareness as a moderating variable among millennials in Surabaya. This study employed the quantitative approach analysed with Smart PLS 4, which aims to determine the impact of religiosity on Political Participation, and whether Social Awareness intervenes in the effect. In this study, a survey was conducted on 284 respondents. The samples are calculated using the Lemeshow formula because the population size of Christian Millennials in Surabaya is unknown.